Semantics of Wainamoinen’s Proper Names in Kalevala - BULINA, Evgeniya Nicolaevna; SOLNYSHKINA, Marina Ivanovna; BAHTIOZINA, Marina Georgievna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article presents semantic analysis of proper names of Wainamoinen, one of the major characters of the Finnish epos Kalevala. The comparative analysis revealed the following layers of information in Wainamoinen’s proper names: a transparent inner form of names (Väinämäinen / Wainamoinen, Väinö / Waino, Suvantolainen / Suwantolainen, Uvantolaynen, Osmoynen, Kalevainen, Kalevalainen) of finnish origin, language and lack of transparency of Wainamoinen’s names in English, an additional connotation formed by the morphological structures of the names and a social status, dependent on the relationship of the addresser and the addressee. RESUMEN El artículo presenta un análisis semántico de los nombres propios de Wainamoinen, uno de los personajes principales del epos finlandés Kalevala. El análisis comparativo reveló las siguientes capas de información en los nombres propios de Wainamoinen: una forma interna transparente de los nombres (Väinämäinen / Wainamoinen, Väinö / Waino, Suvantolainen / Suwantolainen, Uvantolaynen, Osmoynen, Kalevainen, Kalevalainen) de origen finlandés, lenguaje y falta de transparencia de los nombres de Wainamoinen en inglés, una connotación adicional formada por las estructuras morfológicas de los nombres y un estatus social, dependiente de la relación del remitente y destinatario.